Analisa Penentuan Harga Pokok Produksi Pada Fabrikasi Skid Winch System dengan Metode Job Order Costing (Studi Kasus Pada Perusahaan Manufaktur dan Konstruksi) - Rinda Fitriana; Rina Sandora; RA Norromadani Yuniati (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the company that growing is company that focus in fabrication and construction. Inthese company consist of some division, one of division is production division. At this time thecompany is producing skid winch system. In determining the calculation of cost of good sold of thecompany experiencing mismatch budget plan costs and cause the company does not get the maximumprofit. In determining of the cost of good sold based on the right and accurate order appropriate tothe working system in the company is job order costing method. The method can calculate allclassification cost, there are direct and indirect costs. the classification is charged to the orderedproduct. Based on the results of the research cost of good sold of 1 unit skid winch system based onjob order costing method is Rp. 37.564.984, - and the selling price is Rp. 51.651.853, -.and the Profitis Rp. 9.391.246, -. the calculation using job order costing method with company calculation there iscost difference, cost of good sold equal to Rp. 5.665.388,- and the calculation of selling price Rp.16.551.298,-. This is because the company in the determination of the cost of good sold and theselling price does not classify all components of the cost in detail so the result that got by thecompany are less accurate and less maximum profit.